Vaccination Status of Children With Epilepsy or Cerebral Palsy in Hunan Rural Area and a Relative KAP Survey of Vaccinators - Yang, Li; Peng, Jing; Deng, Jing; He, Fang; Chen, Chen; Yin, Fei; Zhang, Shujun (Frontiers in Pediatrics, 2019)
Background In China, the vaccination of children with epilepsy(EP) and cerebral palsy(CP) has no protocol eligible to follow. Parents often concern that vaccination to their children could cause complications due to negative recommendations from vaccinators, eventually lead to vaccination declining. Therefore, it is essential to investigate the vaccination status of these specific population, and the knowledge, attitudes, and practices (KAP) of the vaccinators. Methods This study contains two parts. For vaccination status, residency and age-matched children whose medical expenditure were covered by the New Rural Cooperative Medical System in Hunan Province were enrolled. Children who diagnosed as EP or CP were included as the case group. Children without any chronic disease were enrolled as the control group. Their vaccination rates were compared. For the KAP survey, vaccinators who registered in Hunan CDC were recruited as respondents, questions related to the vaccination toward the children with EP or CP were asked. Results The vaccination rates of the case group were significantly lower than the control group (P＜0.001) except BCG and Hep B1. Nine measles and two mumps cases were diagnosed in the case group while there was no Vaccine Preventable Disease(VPD) in the control group. The vaccinators’ knowledge on the issues of vaccination toward children with EP or CP was weaker than general vaccination issues. Seizure-free periods and EEG status were their most concern to make a vaccination decision. Conclusion The vaccination status of rural children with EP and CP is in jeopardy in Hunan, China. There are several misunderstandings about the contraindications of vaccines among the vaccinators. A series of measures should be taken to improve this situation.